Interfaith convergence in environmental action: comparative analysis of christian and islamic ecological responses - Berthin S. Banga; Yane R. Maahury; Kevin S. Purba (Lentera Negeri, 2026)
The ecological crisis in Sentani District, Papua, including the 2019 flash flood, pollution of Lake Sentani, land-use change, waste accumulation, and forest degradation, shows the need to examine how religious values are translated into ecological responsibility. Addressing the empirical gap in studies that often discuss religion and ecology at doctrinal or global levels, this study examined and compared how Christian and Muslim communities in Sentani interpret ecological degradation and transform religious teachings into environmental action. The study employed a qualitative multiple case study design with two cases: Christian ecological praxis and Islamic ecological praxis. Informants were selected purposively from religious leaders, environmental practitioners, and congregation members who were actively involved in religious and ecological activities. Data were collected through in-depth interviews, participatory observation, and documentary analysis, and were analyzed using within-case analysis, cross-case analysis, and thematic analysis. Credibility was strengthened through data triangulation, saturation-oriented recruitment, an audit trail, peer debriefing, and member checking of key interpretations. The findings showed that ecological degradation was understood as both an environmental problem and a moral-spiritual crisis. Christian ecological responsibility was grounded in imago Dei, stewardship, and Genesis 2:15, while Islamic ecological responsibility was articulated through amanah, khalifah, cleanliness, moderation, and the prevention of fasad. Churches and mosques functioned as pedagogical and social spaces that shaped ecological awareness through preaching, education, worship, and collective action. This study concludes that faith-based ecological praxis can support contextual and sustainable interfaith environmental collaboration in Sentani.